Retrieving answers from multiple documents using semantic skolem indexing - Varathan, Kasturi Dewi; Tengku Sembok, Tengku Mohd; Omar, Nazlia; Abdul Kadir, Rabiah (IEEE, 2011)
The representation of document content is very important factors in retrieval process. The failure to create a good knowledge representation will definitely lead to failure in terms of its retrieval no matter how good the retrieval engine is. Therefore, this research focused on creating a reliable knowledge representation for our retrieval engine. We are using skolem to capture the information conveyed by multiple text documents and used skolem as an index language. This research also focuses on utilizing the skolem index as its knowledge representation in its question answering system. The system is capable of retrieving the answer as well as states the exact document in which the answer is derived from.